Implementasi Percepatan Sertifikasi Tanah Wakaf Dalam Mengurai Konflik Agraria di Kecamatan Siliragung Kabupaten Banyuwangi - Nasobi Niki Suma (Jurnal Al-Tatwir, 2022)
The implementation of waqf is still mostly done in a way of mutual trust. This phenomenon makes waqf land not have strong agrarian legal legality and is prone to conflict. This condition also occurs in the District of Siliragung, Banyuwangi Regency. So that strategic steps related to accelerating waqf land certification need to be synergized with several parties to prevent agrarian conflicts. This study aims to explain the process of accelerating waqf land certification in Siliragung District, Banyuwangi Regency. In addition, this study also aims to analyze actions to resolve agrarian conflicts in Siliragung District, Banyuwangi Regency. The research method used in this research is descriptive qualitative. The results showed that the process of accelerating waqf land certification in Siliragung District was by forming a task force team for accelerating waqf certificates, measuring and recording waqf land, making mass waqf pledges at Baiturrohman Mosque and inputting data to SIWAK (Waqf Information System). Actions to prevent agrarian conflicts are synergizing and collaborating with the Banyuwangi National Land Agency (BPN), the Banyuwangi Nahdlatul Ulama (PCNU) Branch Manager and the Nahdlatul Ulama Branch Council (MWCNU) and the Siliragung Religious Affairs Office (KUA). These Islamic institutions and organizations work together to speed up the process of issuing waqf certificates and making mass waqf pledges. Another action is by socializing waqf and applicable regulations related to waqf to the Islamic community in Siliragung District.